HIBAH DAN PEMBERDAYAAN BANGUNAN BANK SAMPAH DI SULAWESI UNTUK PEMBERDAYAAN MASYARAKAT LOKAL - Ruli Saefudin; Heru Setiyo Cahyono; Zsagheta Ihwalrezky; Danan Eko Cahyono; Annisa' Carina (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
This article analyzes the role of grants and empowerment models through the construction of Bank Sampah buildings/facilities in Sulawesi as instruments for improving the welfare of local communities while addressing waste management issues and providing raw materials for the Waste-to-Energy cluster. The analysis is based on internal documents from PT. Bumi Bersih Berenergi (BT 1.docx) that describe the zero-waste campaign program, operational constraints of the Waste Bank, local landfill practices, and plans for waste processing clustering. The results show a gap between vision and implementation: an urgent need for structured grants—with business conditions, institutional coaching, and market connectivity—as well as technical measures for hazardous waste safety, strengthening the waste value chain, and sustainable cooperative/UBS (waste bank unit) models. The article concludes with policy recommendations and a realistic and measurable grant program design.